Novel influenza polymerase PB2 inhibitors for the treatment of influenza A infection. Issue 20 (15th October 2019) - Zhang, Hongwang; Zhou, Longhu; Amichai, Sarah; Zandi, Keivan; Cox, Bryan; Schinazi, Raymond; Amblard, Franck
Graphical abstract: Abstract: Exploration of the chemical space of known influenza polymerase PB2 inhibitor Pimodivir, was performed by our group. We synthesized and identified compounds 16a and 16b, two novel thienopyrimidine derivatives displaying anti-influenza A activity in the single digit nanomolar range in cell culture. Binding of these unique compounds in the influenza polymerase PB2 pocket was also determined using molecular modeling.